From Classroom to Community: Strengthening Economic Understanding through Problem-Based Learning - M. Sa'i; Prasetyo Adi Nugroho; Abdul Wahid Zaini Wahid Zaini (Al-Qalam Institute, 2025)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) model in improving students’ understanding of local economic potential. Using a qualitative approach with the Classroom Action Research (CAR) method, the study was conducted through four stages: planning, implementation, observation, and reflection. The participants consisted of eighth-grade students enrolled in Social Studies (IPS) subjects. Data were collected through observation, interviews, pre- and post-tests, and student response questionnaires regarding the implementation of PBL. The findings indicate that PBL significantly enhanced students’ critical, collaborative, and analytical thinking skills in understanding local economic dynamics. The increase in average scores from pre-test to post-test demonstrates a measurable improvement in students’ conceptual mastery. Furthermore, students’ active involvement in creating a local economic map strengthened their ability to connect theoretical knowledge with real-life economic practices in their surroundings. This study concludes that implementing PBL in social studies effectively promotes contextual economic literacy and fosters socio-economic awareness among junior high school students.